2013
DOI: 10.5455/ijmsph.2013.2.374-377
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of parenteral iron sucrose complex therapy in iron deficiency anemia in antenatal and postnatal women

Abstract: Background: Iron deficiency anaemia (IDA) is one of the common medical disorders in pregnancy in the developing world, which affect both the mother and the newborn and subsequent child and later adult. Aims & Objective: This study is undertaken to evaluate the safety and efficacy of parenteral iron sucrose complex therapy in iron deficiency anaemia in antenatal and postnatal women. Material and Methods: 110 consecutive pregnant women between 16-36 weeks of gestation and postnatal women, diagnosed as cases of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…[ 11 12 13 14 15 16 17 18 ] Nonetheless, our finding is well within the range of reported increase in Hb level of 1.6 g/dL to 3.6 g/dL. [ 11 12 13 14 15 16 17 18 ]…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[ 11 12 13 14 15 16 17 18 ] Nonetheless, our finding is well within the range of reported increase in Hb level of 1.6 g/dL to 3.6 g/dL. [ 11 12 13 14 15 16 17 18 ]…”
Section: Discussionsupporting
confidence: 89%
“…[ 14 ] In most of the published literature, an additional amount of 500 mg of iron was added to the calculated iron deficit for replenishing body iron reserve. [ 11 12 15 17 18 ] The maximum increase in Hb level (3.6 g/dL) was seen in a study that had added 1000 mg of iron for replenishment of iron store. [ 14 ] In our study, only 16.4% of moderately anemic pregnant women became nonanemic after receiving IVIS, and more than half (57.8%) of them remained in the same category even after receiving IVIS in recommended dose.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of moderate or severe adverse reactions requiring treatment or discontinuation of IV iron was slightly higher in observational studies (13/1352; 9.6 per 1000 women; n = 20 studies) 12,13,19,20,22,23,32,33,40,41,44- [11][12][13][14][15][16]19,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][44][45][46][47][49][50][51] or FCM (1/276; 3.6 per 1000).…”
Section: 38mentioning
confidence: 99%
“…The majority of studies involved a comparison group of some kind including oral iron (n = 17; 36%), 11,14,16,19,24,26,27,29,31,32,34,35,37,39,50,56,57 IV iron (n = 4; 9%), 13 [14][15][16]18,20,24,26,28,31,[33][34][35][36][37][38][39]41,42,44,49,50,53 Only one study was identified that directly compared the administration of a full replacement dose of IV iron to a dose that was 300 mg less than the calculated full replacement dose. In comparing the two groups, administration of the full replacement dose was associated with a greater increase of 8 g/L 3-4 weeks after administration and 14 g/L at delivery.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…There were no major adverse reactions. 11 Neeru S et al rise in mean Hb was 2.06 gm%. 12 In Al-Memon AK et al rise in mean Hb was 2.5 gm% and rise in mean MCV was 10 ft. 13 In Kiran KV et al rise in mean Hb was 2.53 gm%.…”
Section: Resultsmentioning
confidence: 99%